Pengaruh Ekstrak Bengkuang (Pachyrhizus erosus) terhadap Kadar Kolesterol Total Darah Tikus Putih (Rattus norvegicus) yang Diberi Diet Tinggi Lemak - Atma Sanggani Tunikasari; . Suhanantyo; Ruben Dharmawan (Nexus Biomedika, 2014)
Background : Cardiovascular disease is the leading cause of disability and death in the world. High levels of blood cholesterol becoming a risk factor in atherosclerosis is the leading cause of cardiovascular disease. Yam Bean contains flavonoids, isoflavones, phenols, and saponins which have an effect of antihyperlipidemia. This study aimed to determine the effect of Yam Bean (Pachyrhizus erosus) extract on blood total cholesterol level of rats (Rattus norvegicus) with a high fat diet. Methods : This research was an experimental laboratoric research using the post test only with control group design. The research subject were 30 male white rats, Sprague Dawley strain, 2 months old, and their weights were about 130-240 gram. The subjects were arranged into 6 groups. The whole groups were adapted for 7 days. All groups except normal control, were administered high fat diet 2 ml/200 gram BW/day for 21 days. The positive control group was administered 0.18 mg/200 g BW/day of simvastatin and the negative control group was administered 2.00 ml/200 g BW/day of distilled water. While the first, second and third treatment groups were consecutively administered 70 mg, 140mg and 210 mg/200 g BW/day of Yam Bean extracts. On the 22nd day, the blood samples of the subjects were taken from pre-orbital plexus for measurement of cholesterol levels. Then, the data were analyzed using One-way ANOVA test and Least Significance Difference test (LSD). Results : The One-way ANOVA test showed a significant difference in blood total cholesterol level among six groups (p = 0.001). Post Hoc Test showed a significant difference among two groups, except the third treatment group which had the same result and the normal control groups (p = 0.335). Conclusion : Yam Bean (Pachyrhizus erosus) extract had effect to decrease the blood total cholesterol levels of rats. Keywords : Yam Bean (Pachyrhizus erosus) extract, total cholesterol levels, white rats.